PENANAMAN NILAI-NILAI MODERASI BERAGAMA KEPADA PESERTA DIDIK MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Amatul Jadidah (CV. ADIBA AISHA AMIRA, 2024)
There is a need for an understanding to stop the attitudes of extremism and liberalism, which are ideologies that lie in the middle ground, neither leaning towards extremism nor liberalism. These excessive attitudes can trigger religious conflicts that will threaten national sovereignty. The cultivation of religious moderation values in Islamic religious education for students at schools is important to enhance awareness and understanding of the meaning of diversity around them. The instilling of religious moderation values can be seen in several inclusive and tolerant religious activities. The values of religious moderation include tawassuth, fairness or proportionality, tolerance, peace, unity and brotherhood, nationalism, equality or equity, and other values. The role of Islamic religious teachers in instilling religious moderation in educational institutions is very important, as teachers have the role of providing a broad understanding and appreciation of Islam as a religion that is a blessing for all creation and that values differences.